The decline of pile-dwellings at Ljubljansko barje - Velušček, Anton; Toškan, Borut; Čufar, Katarina (Arheološki vestnik, 2011)
The article presents the results of archaeological, dendrochronological, and archaeozoological research at four pile-dwelling settlements at the Ljubljansko barje, at the previously investigated Založnica and at the newly discovered Črni graben, Dušanovo, and Blato. During 2009 and 2010, we had documented and sampled archaeological finds (pottery), wooden remains of piles driven into the ground, on which the pile-dwellings were built, and animal bone remains. Dendrochronological analysis was performed on the samples of wood, comprising over 45 tree rings. The determinability of animal bones was high as expected (NISP = 42 at N = 70). Wood samples from Založnica, which was inhabited during the century prior to 2400 BC, were dated to the period between 2459 and 2457. Ash wood at Črni graben was mostly cut down in 2491 BC. The wood from the sites of Dušanovo and Blato could not be analysed because it had too few tree rings or was not sufficiently preserved. The archaeological finds at Založnica, Črni graben, and Dušanovo are assigned to the Somogyvár-Vinkovci culture. The pile-dwelling of Blato is later and most probably dates to the Middle Bronze Age. Thus it belongs to the group of similar settlements that mark the end of the pile-dwelling era at the Ljubljansko barje. The species composition of the animal remains sample, with a significant representation of hunted species, is also in line with such a time definition. A bovine phalange from the pile-dwelling of Črni graben reveals deformations that can be connected to the use of these animals as working animals.